SISTEM PENGENDALIAN INTERNAL PENERIMAAN DAN PENGELUARAN KAS PADA BIRO ADMISI DAN PEMASARAN - Sahara, Meliana; Farina, Khoirina (Fakultas Ekonomi, Program Studi Akuntansi, 2021)
This research to find out how to implement the internal control system for cash receipts and disbursements, to evaluate the internal control system for cash receipts and disbursements and to compare the internal control systems for cash receipts and disbursements at the Admissions and Marketing Bureau with the internal control system for cash receipts and disbursements according to the Committee of Sponsoring theory. Organization Of Treadway Commission.The type of data used in this study is qualitative data, where the data used in this study are primary data and secondary data. The research method used in collecting data in this study is the field research method. While the analysis method used in this research is descriptive analysis method.The results of this study can be concluded by the authors, that the implementation of internal control of cash receipts and disbursements at the Admissions and Marketing Bureau is considered not optimal with the components of the internal control system according to the Committee Of Sponsoring Organization Of Treadway Commission, so that the system of cash receipts and disbursements must be arranged in detail. to support the implementation of cash receipts and disbursements in a more orderly, integrated, effective and efficient manner.Keywords: Internal Control System, Cash Receipts, Cash Disbursements.